Death of the black widow - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Grand Central Publishing, 2022)
"On his first night with Detroit PD, Officer Walter O'Brien is called to a murder scene. A terrified twenty-year-old has bludgeoned her kidnapper with skill that shocks even O'Brien's veteran partner. The young woman is also a brilliant escape artist. Her bold flight from police custody makes the case impossible to solve--and, for Walter, even more impossible to forget"--